Individualized Scan Protocols in Abdominal Computed Tomography: Radiation Versus Contrast Media Dose Optimization. Issue 6 (June 2022) - Martens, Bibi; Jost, Gregor; Mihl, Casper; Nijssen, Estelle C.; Wildberger, Joachim E.; Schmidt, Bernhard; Flohr, Thomas; Pietsch, Hubertus
Abstract : Background: In contrast-enhanced abdominal computed tomography (CT), radiation and contrast media (CM) injection protocols are closely linked to each other, and therefore a combination is the basis for achieving optimal image quality. However, most studies focus on optimizing one or the other parameter separately. Purpose: Reducing radiation dose may be most important for a young patient or a population in need of repetitive scanning, whereas CM reduction might be key in a population with insufficient renal function. The recently introduced technical solution, in the form of an automated tube voltage selection (ATVS) slider, might be helpful in this respect. The aim of the current study was to systematically evaluate feasibility of optimizing either radiation or CM dose in abdominal imaging compared with a combined approach. Methods: Six Göttingen minipigs (mean weight, 38.9 ± 4.8 kg) were scanned on a third-generation dual-source CT. Automated tube voltage selection and automated tube current modulation techniques were used, with quality reference values of 120 kVref and 210 mAsref . Automated tube voltage selection was set at 90 kV semimode. Three different abdominal scan and CM protocols were compared intraindividually: (1) the standard "combined" protocol, with the ATVS slider position set at 7 and a body weight–adapted CM injection protocol of 350 mg I/kg body weight, iodine delivery rate (IDR) of 1.1 g I/s; (2) the CM dose-saving protocol, with the ATVS slider set at 3 and CM dose lowered to 294 mg I/kg, resulting in a lower IDR of 0.9 g I/s; (3) the radiation dose-saving protocol, with the ATVS slider position set at 11 and a CM dose of 441 mg I/kg and an IDR 1.3 g I/s, respectively. Scans were performed with each protocol in arterial, portal venous, and delayed phase. Objective image quality was evaluated by measuring the attenuation in Hounsfield units, signal-to-noise ratio, and contrast-to-noise ratio of the liver parenchyma. The overall image quality, contrast quality, noise, and lesion detection capability were rated on a 5-point Likert scale (1 = excellent, 5 = very poor). Protocols were compared for objective image quality parameters using 1-way analysis of variance and for subjective image quality parameters using Friedman test. Results: The mean radiation doses were 5.2 ± 1.7 mGy for the standard protocol, 7.1 ± 2.0 mGy for the CM dose-saving protocol, and 3.8 ± 0.4 mGy for the radiation dose-saving protocol. The mean total iodine load in these groups was 13.7 ± 1.7, 11.4 ± 1.4, and 17.2 ± 2.1 g, respectively. No significant differences in subjective overall image or contrast quality were found. Signal-to-noise ratio and contrast-to-noise ratio were not significantly different between protocols in any scan phase. Significantly more noise was seen when using the radiation dose-saving protocol ( P < 0.01). In portal venous and delayed phases, the mean attenuation of the liver parenchyma significantly differed between protocols ( P < 0.001). Lesion detection was significantly better in portal venous phase using the CM dose-saving protocol compared with the radiation dose-saving protocol ( P = 0.037). Conclusions: In this experimental setup, optimizing either radiation (−26%) or CM dose (−16%) is feasible in abdominal CT imaging. Individualizing either radiation or CM dose leads to comparable objective and subjective image quality. Personalized abdominal CT examination protocols can thus be tailored to individual risk assessment and might offer additional degrees of freedom.